Synthesis of silver nanoparticles using supercritical water - B, Buyankhishig; B, Narandalai; S, Enkhtuul (Bulletin of the Institute of Chemistry and Chemical Technology, 2018)
Supercritical water (SCW) technology is a relatively novel and green method compared with others for the synthesize of metal nanoparticles. It is considered one of the most suitable methods for loading nanoparticles in surface of porous materials due to the water in supercritical conditions has a high diffusivity, well dispersive and it has a same carrier characteristic as like a gas. Silver nanoparticles and silver loaded activated carbons were synthesized using silver acetate solution under supercritical water condition at 4000C and 31.15 MPa in a batch reactor. This study was investigated effect of operational parameters on the particle size of silver nanoparticles in particularly the concen-tration of silver salt solution and the reaction time. The experiments were carried out to test the silver salt concentra-tion at 0.01 M, 0.02 M, 0.05M, and the reaction time of 15 and 30 minutes. When the silver acetate concentration and reaction time increased agglomerations of silver particles were observed on the surface of activated carbons. The structure, morphology and particle size of synthesized products were determined by X-ray diffraction (XRD), Scan-ning electron microscope (SEM) and Transmission electron microscope (TEM). Суперкртитик усан орчинд мөнгөний нанопартиклыг гарган авах Хураангуй: Суперкритик усны арга нь металлын нанопартикл гарган авах бусад аргуудтай харьцуулахад харьцангуй шинэ арга юм. Суперкритик нөхцөл дахь ус нь диффузийн коэффициент өндөртэй, тархалт сайтай, хийтэй адил зөөж тээвэрлэх шинж чанар үзүүлдэг тул сүвэрхэг материал дээр нанопартикл үүсгэхэд тохиромжтой аргуудын нэг гэж үздэг. Мөнгөний нанопартикл болон идэвхжүүлсэн нүүрсэн дээр суулгасан мөнгөний нанопартиклыг суперкритик усны аргаар мөнгөний давсны усан уусмал хэрэглэн гарган авсан. Мөнгөний нанопартиклыг гарган авахад нөлөөлөх гол хүчин зүйлүүдэд хамаарах мөнгөний давсны уусмалын концентрац болон урвал явагдах хугацааны нөлөөг судалсан бөгөөд концентрацыг 0.01 М, 0.02 М ба 0.05 М, харин урвал явагдах хугацааг 15 ба 30 минут гэсэн нөхцөлүүдэд туршилтыг явуулсан. Урвал явагдах хугацаа болон мөнгөний давсны уусмалын концентрац ихсэхэд үүссэн мөнгөний жижиг хэсгүүдийн бөөгнөрөл илүү нэмэгдэж байсан. Гарган авсан материалуудын талст бүтэц, түүний хэмжээ болон морфологийн шинж чанарыг рентген дифрактометр (XRD), сканнинг электрон микроскоп (SEM) болон нэвтрүүлэлтийн электрон микроскоп (TEM) ашиглан тодорхойлсон. Түлхүүр үг: Суперкритик ус, мөнгөний нанопартикл, урвал явагдах хугацаа, уусмалын концентрац.